Geografske dimenzije naravnih nesreč in varstva pred njimi - Natek, Karel (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
From the geographical point of view, natural hazards are not exceptional natural events but part of complex interrelations between nature and society. In geography, they are considered as constituent parts of geographical space and it is possible, by means of geographical methods, to identify their presence, impact on nature and society and possible human adaptations. Such investigations are of vital importance for prevention of their negative effects and as a precondition for responsible spatial planning and implementation of the sustainable development paradigm.
Keywords: Slovenia; Slovenija; pokrajinska ekologija; ranljivost okolja; naravne nesreče; ogroženost; sonaravni razvoj